Comparative Outcomes of Salvage Therapy in Relapsed and Refractory Hodgkin and Non-Hodgkin Lymphomas in Iraq - Hassan, Rasha; Alwan, Alaa Fadhil (Middle Eastern Cancer and Oncology Journal, 2026)
Lymphoma is a relatively treatable cancer, characterized by a favorable prognosis. Nevertheless, between 10% and 25% of patients will exhibit primary refractory or recurrent illness, despite the implementation of risk-adapted treatments. The objective of this study is to assess the response of Hodgkin and non-Hodgkin lymphoma to salvage therapy. A retrospective cohort study was conducted, encompassing 110 patients diagnosed with refractory/relapsed Hodgkin's lymphoma (HL) and non-Hodgkin lymphoma (NHL). The study period spanned from March 2022 to October 2022. Patient demographic and clinical data were meticulously collected for the purpose of analysis. The patients received salvage therapy and were closely monitored to assess their response to the treatment. The results indicate a mean age of 36.07 years ± 14.028 years. Of the patients in the study, 59 (53.6%) were diagnosed with Hodgkin's lymphoma (HL), while 51 (46.4%) were diagnosed with non-Hodgkin's lymphoma (NHL). The most prevalent type of HL was nodular sclerosis, accounting for 38 cases (64.4%). The majority of NHL cases were classified as DLBCL (41 cases, 80.4%). Subsequent to the administration of initial line management, the relapse rate was found to be 48.2%, while the refractory rate was determined to be 51.8%. Following the administration of second-line management, the complete/partial response rate was found to be 73.6%, with a significant association observed between this response rate and Hodgkin's lymphoma (HL). Patients were treated with ABVD as a first-line therapy and ICE as a second-line therapy. In addition, the relapse rate following second-line management was 26.4%, exhibiting a significant association with non-Hodgkin's lymphoma (NHL) with a p-value less than 0.05. For HL, the most effective salvage protocol was identified as ICE, while for NHL, no significant difference was identified among salvage protocols.
Keywords: Salvage Therapy; Relapses; Refractory; Hodgkin Lymphomas; Non-Hodgkin Lymphomas